Recruitment Competition and Labor Demand for High-Skilled Foreign Workers - Morgan Raux (Institute of Labor Economics (IZA), 2023)
This paper estimates the causal effect of recruitment competition on the labor demand for high-skilled foreign workers. I assemble a new data set, combining a firm-level panel of all Labor Condition Applications (LCAs) submitted as a first step to obtaining H-1B visas between 2010 and 2019 with online job vacancies and data on venture capital (VC) investments. I use plausibly quasi-exogeneous variation in VC investments in start-ups to instrument yearly changes in recruitment competition at the local labor market level. I find that a one standard deviation increase in the number of job postings advertised by start-ups yields an 8 percent increase in the number of LCAs submitted by employers in the market and a 3 percent increase in the wages advertised in these LCAs. Estimates are only significant for computer occupations. These results support the role of labor market tightness in explaining the absence of the crowding-out effect from H-1B workers against close native substitutes.
Keywords: F22; J23; J61; 330; labor market tightness; skilled workers; H-1B